Estudo Cromatográfico, Espectroscópico e Farmacológico de Alcaloides Plumeranos das Sementes de Aspidosperma pyrifolium Mart - Nogueira, Patricia Coelho do Nascimento (2014)
This work reports the phytochemical analysis from seeds of Aspidosperma pyrifolium (Apocynaceae), describing the isolation and the structural characterization of a unknown alkaloid with a rearranged plumeran skeleton, the (-)-(3S,7S,21R)-rel-(3αH)-15(14→3)-abeo-2,16,17,20,6,7-hexahydro-15H,8aH,16a,20a-ethano-1H-indolizino[3,1-cd]carbazole, in addition to eleven known compounds, six plumeran alkaloids identified as aspidospermine, demethoxyaspidospermine, pirifoline, 15-demethoxypirifoline, aspidofractinine and N-acetylaspidofractinine; a tetrahydro-β-carboline alkaloid, the N-methylakuammidine; the glycosides of two iridoids, loganic acid and loganin; a salycilic acid derivative, 2-hydroxy-3-O--D-glucopyranosylbenzoic acid; and a methyl inositol derivative, the 2-O-methyl-L-chiro-inositol. The compounds were isolated by chromatographic techniques, especially High Performance Liquid Chromatography, and their structures were characterized by 1D and 2D NMR spectroscopy, FT-IR and HRESIMS, and comparison with data from literature. Altough already reported in the literature, five compounds are being reported for the first time for the species, and one is being reported from a natural source. The NMR data, and the correspondent assignments of some alkaloids already reported in the literature, together with a bibliographic survey (from 1973-2013) of the 13C NMR data of plumeran alkaloids isolated from the Apocynaceae family, are presented in this work. The residual aqueous fraction of the liquid-liquid partition of the ethanol extract from seeds of A. pyrifolium, source of most compounds isolated, showed antinociceptive and anti-inflammatory activities in the formalin test, abdominal writhing induced by acetic acid, and paw edema induced by carrageenan.